Genetic Variation of F2 Progeny Test Acacia auriculiformis A. Cunn. Ex Benth. at KHDTK Blok Playen, Gunungkidul - Katon Dewanto, Prasojo; Supriyadi, Supriyadi; Nufus, Malihatun; Siwi Yuliastuti, Dwi (Jurnal Riset Biologi dan Aplikasinya, 2025)
Acacia auriculiformis is one of a priority species for forestry in Indonesia. This species has great potential. Breeding of the A. auriculiformis species in KHDTK Blok Playen, Gunungkidul, has reached the second-generation breeding cycle. Further evaluation of the A. auriculiformis progeny test planting in KHDTK Block Playen is needed to develop a certified and more optimal seedling seed orchard.  This study aimed to evaluate the growth of 9-year-old A. auriculiformis progeny test in KHDTK Blok Playen, Gunungkidul. Data collection of tree growth included total height, diameter, branch-free stem height, and stem straightness. Measurements were conducted using the census method on 30 families with four tree plots in 12 blocks of F2 A. auriculiformis progeny test at the KHDTK Blok Playen.  The results of the analysis of variance show that the family source of variation significantly affected the four growth characteristics observed. These results indicate that genetic factors greatly influence the diversity or variation in the measured characters. Strong phenotypic correlation was found between height with diameter character (0,569) and the branch-free stem height with a stem-straightness (0,633). In general, the family and individual heritability values ​​in this study were classified as high. The genetic gain from individual selection (within plot selection) at 25% intensity showed moderate to very high values, ​​ranging from 3.123%-16.494% for the four observed characteristics.